Oral History Program Interview: Lillie Ruth Ann Counts Dunn - Lillie Ruth Ann Counts, Dunn
Dunn, born on February 14, 1908, left Porum, Muskogee County, Oklahoma and came to Tulare, California in January 1931. Her story is very different because she was labeled a communist for her stubborn independence. Her interview describes the way "communist" was used back then, how her children were discriminated because of a communist label, what the CCC and WPA did for people, and problems organizing cotton workers.